Establishing Diagnostic Reference Levels for CT Through a Provincial Medical Informatics Metadata Repository in Ontario. Issue 4 (November 2021) - MacGregor, Kate; Concepcion, Lianne; Dowdell, Tim; Gray, Bruce
Purpose: To determine whether computed tomography radiation dose data could be captured electronically across hospitals to derive regional diagnostic reference levels for quality improvement. Methods: Data on consecutive computed tomography examinations from 8 hospitals were collected automatically in a central database (Repository) from April 2017 to September 2017. The most frequently performed examinations were used to determine the standard protocols for each hospital. Diagnostic reference levels across hospitals were derived using statistical distribution for 2 radiation dose metrics. These values were compared between hospitals, within and between hospitals by scanner and against national Health Canada achievable doses and diagnostic reference levels. Results: Three master protocol groups, Head, Abdomen–Pelvis, and Chest–Abdomen–Pelvis, accounted for 43% of all valid studies (N = 40 277). For the Repository, 11 of 12 mean values and 75th percentile diagnostic reference levels were below the Health Canada mean and 75th percentile values, and one was the same as the Health Canada value. Mean radiation dose by protocol varied by as much as 97% between hospitals. There was no consistent pattern in the difference between mean doses between large and small hospitals. Conclusion: This electronic data acquisition process could be used to continually update achievable doses for frequently used computed tomography examinations in Ontario and eliminate the need for nationwide manual surveys. Results compared across institutions will allow hospitals to maintain achievable doses and lower patient exposure.